Estudo da influência da modificação da caulinita na adsorção de eteramina - Leal, Paulo Vitor Brandão (2016)
With the ever more imminent risk of lack of water, the preservation of water resources reaches beyond the context of economy for future generations. Thus, the concern on the importance of its conscious use, as well as the search for the treatment of effluents, has increased. In this context, this work consisted of performing modifications on in natura kaolinite (KN) by means of acid treatment (KA-01, KA-02 and KA-05), treatment with peroxide (KP) and intercalation with dimethyl sulfoxide (KDMSO), with the objective of increasing the efficiency in the adsorption of etheramine, cationic collector employed in the reverse flotation of iron ore. The process of etheramine adsorption onto in natura and modified kaolinite was studied from the combination between planning and optimization by response surface. The systems were adjusted to the quadratic model for the Central Composite Design. We evaluated the effects of the initial concentration of adsorbate, adsorbent mass of 0.1 g for KN and solution pH. The results revealed that the adsorption was more efficient in the etheramine concentration of 400 mg L -1 , pH 10 and adsorbent mass of 0.1 for KN, and etheramine concentration of 400 mg L -1 , pH 10 and adsorbent mass of 0.2 g for the remaining samples. The adsorption kinetics conducted under optimized conditions showed that the system reached balance in approximately 30 minutes. The kinetic data were better adjusted to the pseudo-second order model. The adjustment of the experimental data to the isotherm models revealed that the Sips model was more adequate. The calculation of E ads allowed us to infer that the mechanism for etheramine removal by kaolinite is chemisorption. The tests for reuse showed that, after four uses of adsorbents, the efficiency for removing etheramine suffered no significant modifications, fact that makes feasible a possible use for kaolinite for the treatment of effluents. Based on the theoretical study conducted, it was possible to understand the intercalation process. In addition to increasing the interlayer spacing, the input of dimethyl sulfoxide molecules contributed for the optimization process of adsorption.